2018
DOI: 10.3390/sym10040109
|View full text |Cite
|
Sign up to set email alerts
|

TPVR: User Interaction of Third Person Virtual Reality for New Presence and Experience

Abstract: This study proposes the interaction of third-person virtual reality (TPVR) to provide users with a new presence and experience during immersive virtual reality (VR). The proposed TPVR interaction consists of the ability to directly control the virtual environment and objects by utilizing the hands. For this purpose, this study defines the interaction of TPVR from three types: moving inside the virtual environment, selecting virtual objects and using a menu interface that includes a variety of functions and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Therefore, the current study does not deal with comparative analysis experiments by designing various interfaces and various systematic and environmental factors. However, we confirmed that the interface that interacted with a virtual environment or objects by directly using the hands based on the existing study [3,52] provided enhanced presence through high immersion compared with the input methods of typical interactive systems utilizing gamepads and keyboards. Existing studies on the asymmetric VR including this study mainly focused on the objective performance analysis of the proposed interfaces by using verified questionnaires (e.g., PQ, GEQ) rather than comparing existing studies as the experience environment and conditions presented were clear.…”
Section: Limitation and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, the current study does not deal with comparative analysis experiments by designing various interfaces and various systematic and environmental factors. However, we confirmed that the interface that interacted with a virtual environment or objects by directly using the hands based on the existing study [3,52] provided enhanced presence through high immersion compared with the input methods of typical interactive systems utilizing gamepads and keyboards. Existing studies on the asymmetric VR including this study mainly focused on the objective performance analysis of the proposed interfaces by using verified questionnaires (e.g., PQ, GEQ) rather than comparing existing studies as the experience environment and conditions presented were clear.…”
Section: Limitation and Discussionsupporting
confidence: 78%
“…A study by Denisova and Cairn [56] confirmed that the first-person viewpoint where the world is viewed through the eyes of a character increased immersion compared with the third-person viewpoint, regardless of the preferred viewpoint of the users. However, when interaction and an experiential environment optimized for the third-person viewpoint were presented in the immersive VR, comparative experiments with the first-person viewpoint confirmed that this also showed relatively satisfactory presence [52]. Therefore, this study attempted to present an experiential environment that could utilize both the first-and third-person viewpoints to provide satisfactory presence by inducing immersion in a non-immersive experiential environment of non-HMD user interface.…”
Section: Experimental Results and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Sanal gerçeklik ortamlarındaki başka bir önemli noktaya odaklanan Gorisse ve diğerleri (2017), ortama dâhil olan katılımcıların sahip olduğu birinci kişi bakış açısı ile üçüncü kişi bakış açısının bulunma hissi üzerinde anlamlı bir fark yaratmadığını belirtmiştir. Aynı konu üzerine araştırma yürüten Kim, Lee, Kim, ve Kim (2018) ise üçüncü kişi görüş açısının bulunma hissi üzerinde etkisinin olduğunu ifade etmişlerdir. Benzer bir problemle yola çıkan Slater (2018) katılımcıların birinci kişi görüş açısı, ikinci kişi görüş açısı ve gözlemci olarak yer aldıkları bir araştırma gerçekleştirmişlerdir.…”
Section: Bulunma Hissi üZerine Teknik İncelemelerunclassified
“…The creation of various medical environments with healthcare impacts and personalized experiences can be aided by emergent immersive technologies such as VR, augmented reality (AR), mixed reality (MR), or cross reality (XR), which have become popular as the basis of recreational games [40][41][42][43][44][45][46]. While AR, MR, and XR, in general, can provide training, education, relaxation, or entertainment, VR is the medium that presents the opportunity to most efficiently recreate events that are part of personal narratives, to deeply engage the immersed person with the highest sense of presence [47][48][49][50][51], and most efficiently simulate the personal narrative of the self [52]. VR offers not only the opportunity to elicit a strong response to stimuli, but also provides an as if quality, meaning that it can be compared to the real impact of an experience [53].…”
Section: Recreative Immersionmentioning
confidence: 99%